(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the competence of teachers at SMA Al Kautsar Bandar Lampung in utilizing web-based Artificial Intelligence (AI) technology, specifically ChatGPT, to develop more efficient and innovative lesson plans. The training was held offline on September 19, 2024, involving 33 teachers through a participatory training approach. Evaluation results from pre- and post-training questionnaires revealed an increase in participants’ knowledge of AI applications from 90.1% to 100%, with 93.9% readiness to implement the technology in lesson planning. The training positively impacted teachers’ digital literacy and the quality of education at SMA Al Kautsar. Recommendations include conducting advanced training sessions, providing technical assistance, and improving the school’s digital infrastructure to support sustainable AI integration in teaching and learning processes.